The Land-Labour Hypothesis Revised: Wealth, Labour and Household Composition at the South African Frontier - Jeanne Cilliers; Erik Green (African Economic History Network (AEHN), 2017)
Traditional frontier literature identifies a positive correlation between land availability and fertility. A common explanation is that the demand for children as labour is higher in newly established frontier regions compared to older and more densely populated farming regions. In this paper we contribute to the debate by analysing the relationship between household composition and land availability in a closing frontier region, i.e. the Graaff-Reinet district in South Africa's Cape Colony from 1800-28. We show that the number of children present in farming households increased with frontier closure, while the presence of non-family labourers decreased over time. We explain this by, differently from the frontier literature, acknowledging that the demand for family labour was not a function of its marginal productivity and that farmers reacted to differently to diminishing land availability depending on their wealth. Poorer households, which made up the majority of this frontier population, responded to shrinking land availability by employing relatively more family labour, while the wealthiest group underwent capital intensification.
Keywords: J23; N37; N57; 330; South Africa; household composition; agriculture; labour; pre-industrial